Treatable mortality and health care related factors across European countries - Tavares, Aida Isabel (Frontiers in Public Health, 2024)
Introduction Despite the improvements in European health systems, a large number of premature deaths are attributable to treatable mortality. Men make up the majority of these deaths, with a significant gap existing between women and men’s treatable mortality rate in the EU. Aim This study aims to identify the healthcare-related factors, including health expenditures, human and physical resources, and hospital services use associated with treatable mortality in women and men across European countries during the period 2011–2019. Methods We use Eurostat data for 28 EU countries in the period 2011–2019. We estimate a panel data linear regression with country fixed effects and quantile linear regression for men and women. Results The results found (i) differences in drivers for male and female treatable mortality, but common drivers hold the same direction for both sexes; (ii) favorable drivers are GDP per capita, health expenditures, number of physicians per capita, and (only for men) the average length of a hospital stay, (iii) unfavorable drivers are nurses and beds per capita, although nurses are not significant for explaining female mortality. Conclusion Policy recommendations may arise that involve an improvement in hospital bed management and the design of more specific policies aimed at healthcare professionals.